Analysis Bioavtur for Energy Security - Rudy Laksmono Widayatno; Arwin Datumaya W; Zaenal Abidin (The Republic of Indonesia Defense University, 2016)
In 2014, Avtur commodities in Indonesia, recorded a deficit of 0.9 million kiloliters. This situation are not profitable for the country, both economically and energy security. This aim of research is exposing clearly about the condition of national energy resources, the development of biofuels (especially bioavtur) and policies that support the production and use of bioavtur. This study used a qualitative approach with descriptive analysis. Data sources obtained from in-depth interviews with the institutions related to the energy field, air transport, the biofuels industry (bioavtur) and farmer groups/associations of oil palm plantations. The results is there are a variety of biological sources in Indonesia that can be used bioavtur such as algae, pecans, coconut, and palm oil. Opportunities and prospects bioavtur market in Indonesia is promising. Future studies are necessary to improve the economics of the plant-based oil bioavtur because Indonesia has large oil supply source.